2019
DOI: 10.1007/s40122-019-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Factors Associated with Low Back Pain Among Nurse Professionals in East and West Wollega Zones, Western Ethiopia, 2017: A Cross-Sectional Study

Abstract: IntroductionLow back pain (LBP) is yet the persistent public health challenges around the globe. It substantially affects quality of life and poses disability, particularly to the global working population. The profound losses in productivity and compensation premiums due to the condition have also been a challenge to contemporary occupational health. As such, it no doubt demands informed management and due response. The objective of this research was therefore to investigate the prevalence and work-related fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
74
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 24 publications
10
74
0
9
Order By: Relevance
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%